Rancang Bangun Network Attached Storage Sebagai Media Penyimpanan Arsip dan Dokumen Digital di Politeknik Negeri Bengkalis - Sobirin, M; Tedyyana, Agus (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The Public Relations (Humas) Division of Politeknik Negeri Bengkalis has an essential role in external relations and publications, including documenting campus activities. However, the documentation storage process remains scattered across various members’ devices, lacking a centralized storage medium, which poses risks of data loss and makes shared access difficult. This study aims to develop an integrated Network Attached Storage (NAS) system that is secure, cost-effective, and accessible from anywhere. The system was built using an Orange Pi Zero 3 Single Board Computer (SBC) as an alternative to the Raspberry Pi 4 to reduce costs, along with the nextcloud software and the Fail2Ban security mechanism. Testing results show that the NAS can be accessed via both local networks and the internet, with an average transfer speed of 27.5 MB/s (220 Mbps), sufficient for document and archive storage needs. The system proved to be secure against brute force attacks and provided centralized data access convenience. This implementation successfully meets the research objectives by offering a flexible, secure, and affordable storage solution for institutions, while serving as an effective alternative for digital data management.